Empowerment, transformation and the construction of 'urban heritage' in post-colonial Hong Kong - Lu, Tracey L.-D. (International journal of heritage studies : IJHS, 2016)
In recent years, there have been many political and economic debates in Hong Kong, and heritage conservation has been used as a political and economic weapon by some members of the community. Based on participant observation and in-depth interviews, this paper analyses how buildings of a small street built in the 1950s were constructed as 'heritage', and how a community heritage discourse was used by a group of local residents (Kiefang), university students and professionals to object to the urban renewal project led by the Hong Kong government. In this context, heritage was used to obtain political rights and to express anger against the increasing gap between the rich and poor of Hong Kong. Though the immediate objectives of this group were not achieved, the protest process empowered a group of local residents, and has marked the commencement of a politicalized heritage conservation movement in post-colonial Hong Kong.